Application of a green banking performance index to Portugal - Pereira, V. M. M.; Filipe, J. A. C. B. (RISUS - Revista de Inovação e Sustentabilidade, 2021)
This paper reports the calculation of a green banking performance index that considers the importance that banks give to environmental issues. Research was conducted considering all banks authorized to operate in Portugal and similar relevant institutions. The calculated green banking performance index reveals a large difference between the 5 most representative banks and the others. The 5 most representative banks show that, on average, they are very concerned with environmental issues, and the others reveal, on average, a medium level of concern in terms of environmental issues.